Implementing interactive videos based on local cultural values to enhance character education among elementary school students - Muhammad Yusnan; Munirah; Anin Asnidar; Farisatma; Agusalim; Fahril Ramadhani (Universitas PGRI Madiun, 2024)
Implementation of interactive videos based on local cultural values in elementary school character education is essential in face of rapid technological advancement. Interactive videos not only help students understand and appreciate their own cultural heritage, but also introduce them to important character values embedded in local traditions and customs. These values play a crucial role in shaping students’ identity, integrity, and personality. Study aims to apply interactive videos grounded in local cultural values to support character education in elementary school students. A quantitative approach was used, involving a survey of 21 students to evaluate key aspects of character development. Data collected through questionnaires were analyzed statistically to provide an objective overview and to inform the development of effective character education policies. Findings indicate that the use of interactive videos had a positive impact on students’ character development, particularly in the areas of cooperation and environmental awareness, which were mostly rated as